The structure of space: cubism and modernism. Figures and icons in Josef Gočár’s work - Chizzoniti, Domenico Giuseppe (Journal of Architecture and Urbanism, 2017)
This research paper relates to a number of works by Josef Gočár, a Bohemian architect who was active in a time period between “Cubist” vanguardism and “Rationalist” modernism.The theme regards the search for a general method which evaluates the key elements of the structure of space in architectural design. The main asset of architectural composition has traditionally been the close association between the syntactic order of the elements and a semantic perception of space. The aim of this essay is to explore the relation between the role of the experimental design regarding the multiple and changeable architectural experience and the creative process of architectural work.The methodological experience hereby demonstrated refers to a specific case study that belongs to the scientific research carried out by Gočár and his researchers’ group at the Prague Fine Arts Academy (AVU). His work is hereby re-interpreted in an effort to explore the experiential contribution to the architectural design discipline, and the figurative aspect, by reexamining various characteristics of his practical experience as an architect involved in the civic priorities of the city, from the scale of urban settlement to the individual design work.